Monitoring Biomarkers of Drivers with Medical Wireless Sensor Networks Deployed in Connected Vehicles - Karmakar, Sayon; Mohan, Seshadri (Nordic and Baltic Journal of Information & Communications Technologies, 2021)
Millions of traffic accidents occur each year that negatively impacts the economy as well as the human lives. Human error is the principal cause of traffic accidents. Medical conditions of drivers that are not usually monitored have a significant role in accidents. Chronic illnesses have been shown to have reduced cognitive, visual and motor skills, which are the key driving requirements. In conjunction with the current wireless communication technologies and data processing capabilities, it is urgent that suitable sensors be deployed to perform non-invasive detection of objective biomarkers that state the driver’s health. Cellular V2X communication provides the ability to share the information collected to the nearby driving vehicles for cautionary stance and to the hospitals for clinical validation. Dedicated short-range communication (DSRC) allows for the establishment of vehicle-to-vehicle communication (V2V) and vehicle-to-anything communication (V2X). This interconnected setup of Connected Vehicles (CV) would pave the way to establishment of smart city.